Emergency cesarean section rate between women with gestational diabetes and normal pregnant women - Dittakarn Boriboonhirunsarn; Rungnapa Waiyanikorn (Elsevier, 2016)
Objective: Gestational diabetes mellitus (GDM) has been related to various maternal and neonatal complications. The degree to which GDM is related to an increased rate of cesarean section is less certain. This study was aimed at comparing the incidence of emergency cesarean delivery between pregnant women with GDM and normal pregnant women. Materials and methods: The study group consisted of 237 term, singleton pregnant women with GDM. Another 237 uncomplicated, normal pregnant women were randomly selected and served as the comparison group. Those who were scheduled for elective cesarean delivery and overt DM were excluded. Data were retrieved from medical records, including demographic data, antenatal and intrapartum care data, route of delivery, indications for cesarean delivery, and neonatal outcomes. Results: The study group had a significantly higher mean age and body mass index, and the participants were more likely to be overweight/obese. The rate of emergency cesarean delivery was significantly higher in the study group than in the comparison group (31.6% vs. 19.4%, p = 0.002). The study group was more likely to have Cephalo-pelvic disproportion (CPD) (20.3% vs. 13.1%, p = 0.036) as an indication for cesarean delivery. Birth weight was significantly higher (by 200 g) in the study group. When stratified by parity, significant differences in cesarean delivery rates were observed only among nulliparous women. Logistic regression analysis showed that GDM significantly increased the risk of emergency cesarean delivery (adjusted odds ratio 1.9, 95% confidence interval 1.03-3.5, p = 0.039) only among nulliparous women, adjusted for age, body mass index, and gestational weight gain. Conclusion: The incidence of emergency cesarean delivery increased significantly among nulliparous GDM pregnant women, compared with that in normal pregnant women.